2011
DOI: 10.1007/s10344-011-0517-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of odour repellents on red deer (Cervus elaphus) and roe deer (Capreolus capreolus): a field test

Abstract: Chemical repellents are promoted as a method to reduce ungulate-vehicle collisions and ungulate browsing damages to agricultural and forestry resources. We tested the effectiveness of two odour repellents (Mota FL and Wolf Urine) on the foraging behaviour and area avoidance of free-ranging roe deer (Capreolus capreolus) and red deer (Cervus elaphus). The effects of the repellents were assessed by comparing deer visitation rates to sand arenas before and after application of repellents and visitation rates to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 17 publications
3
21
0
7
Order By: Relevance
“…The most probable reason for their frequent ineffectiveness is the fact that the environment around tracks is highly food-attractive for the animals and the applied odours are not able to discourage the animals from being near the railway. Other studies (Elmeros et al 2011;Schlageter and Haag-Wackernagel 2012a, b) came to similar conclusions, i.e. ineffectiveness of odour repellents in places with attractive food for animals.…”
Section: Technical Measuressupporting
confidence: 59%
“…The most probable reason for their frequent ineffectiveness is the fact that the environment around tracks is highly food-attractive for the animals and the applied odours are not able to discourage the animals from being near the railway. Other studies (Elmeros et al 2011;Schlageter and Haag-Wackernagel 2012a, b) came to similar conclusions, i.e. ineffectiveness of odour repellents in places with attractive food for animals.…”
Section: Technical Measuressupporting
confidence: 59%
“…It is therefore not surprising that several studies have reported rapid habituation to predator-born odor in a natural environment (Cox et al 2010, Elmeros et al 2011, Bytheway et al 2013. It is therefore not surprising that several studies have reported rapid habituation to predator-born odor in a natural environment (Cox et al 2010, Elmeros et al 2011, Bytheway et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In a natural environment, the odor of a predator might be abundant in the form of excrement or markings. It is therefore not surprising that several studies have reported rapid habituation to predator-born odor in a natural environment (Cox et al 2010, Elmeros et al 2011, Bytheway et al 2013. This leads to the assumption that prey, while detecting PO, considers it as an ambient risk (Brown et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The use of multiple stimuli that are perceived using different sensory modalities and/or are randomly presented can help maintain novelty and delay habituation; animals are less likely to repeatedly receive the same stimulus or generalize their habituation between different stimuli [Elmeros et al, 2011;Smith et al, 2000]. For example, captive cheetahs (Acinonyx jubatus) showed no signs of habituation when presented with a randomized schedule of temporal, spatial, and olfactory enrichment [Quirke and O'Riordan, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…For example, captive cheetahs (Acinonyx jubatus) showed no signs of habituation when presented with a randomized schedule of temporal, spatial, and olfactory enrichment [Quirke and O'Riordan, 2011]. Implementing randomized schedules with multiple types of stimuli could also reduce habituation and generalization to crop raiding deterrents [Elmeros et al, 2011;Smith et al, 2000].…”
Section: Discussionmentioning
confidence: 99%